Research Progress of Graphene-based Flexible Sensor in Wearable Health Monitoring (Journal of Fiber Bioengineering and Informatics, 2019)
Research of flexible sensors for human wearable health monitoring are of paramount importance. In viewof the problems of traditional sensors, such as complexity, low sensitivity, insufficient strain, short servicelife and incompatibility with human body, the research progress of Graphene-based flexible sensors inwearable health monitoring is systematically introduced. Benefitting from the commendable flexiblemechanical properties and high durability, flexible Graphene-based sensors promote its applications inmotion detection, body temperature monitoring, sweat ion real-time monitoring, voice recognition, pulsebeating, and respiration detection. The challenges and prospects of the application of Graphene-basedflexible sensors in wearable health monitoring are pointed out. It is expected that most current research,which is still experimental, will need several more years of study before it becomes widely used. In thefuture, more attention should be paid to the lack of flexibility and high sensitivity of Graphene, thepreparation of high purity Graphene, the application of composite materials and the development ofadvanced technology.